PENGARUH KOMPETENSI APARATUR PEMERINTAH, KETAATAN PADA PERATURAN PERUNDANGAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KOMITMEN ORGANISASI DAN KINERJA MANAJERIAL SEBAGAI VARIABEL MODERATING (Studi Empiris Pad - Muhammad Hafiz; M. Rasuli '; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to look at the effect of the competence of the government apparatus, adherence to laws and regulations, and budget goal clarity to the accountability of the performance of government agencies with organizational commitment and managerial performance as a moderating variable in the SKPD in Kampar regency. This research was carried out on 33 working units are located in Kampar regency in 2016. The samples were used as respondents drawn using proposive sampling method. Each population is represented by three respondents, chief financial officer, treasurer, and chief of staff of the program. Questionnaires were distributed to 99 respondents, and successfully recovered the complete answer is obtained from 45 respondents. Data collected from 45 respondents further data were analyzed with SPSS version 2.0 using descriptive statistical analysis and multiple linear regression analysis to generate test classic assumptions, data analysis model, the coefficient of determination and prove the hypothesis. The results found that the simultaneous partial or variable competence of the government apparatus, adherence to laws and regulations, and budget goal clarity and organizational commitment and managerial performance as moderating variables affect the performance accountability of government agencies.Keywords: Competence, Obedience, Budget Targets, Commitment, Performance, and Accountability